Effect of grain ultra-refinement on corrosion behavior of ultra-high strength high nitrogen stainless steel. (September 2020) - Zhang, H.; Xue, P.; Wu, L.H.; Song, Q.N.; Wang, D.; Xiao, B.L.; Ma, Z.Y.
Graphical abstract: Highlights: Strength and corrosion resistance of cold-rolled stainless steel were improved. Uniform ultrafine-grained microstructure (∼300 nm) was achieved by water-cooled FSP. Grain ultra-refinement significantly improved repassivation ability. Increased element content of passive film improved pitting corrosion resistance. Abstract: High-performance high nitrogen stainless steel (HNS) with ultra-high strength up to ∼1.7 GPa and excellent corrosion resistance was successfully obtained by friction stir processing. The simultaneous enhancement in strength and corrosion resistance was mainly attributed to the grain ultra-refinement. Uniform ultrafine-grained microstructure (∼225 nm) significantly improved the repassivation behavior of HNS. With significantly increased element diffusion rate and element content, the passive film formed on the ultrafine-grained HNS showed high resistance to the nucleation and growth of pits. Grain ultra-refinement was confirmed to be an effectual method for improving corrosion resistance of HNS without sacrificing strength.